RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY EMONE 26 (BRASSICA RAPA L.) PADA PEMBERIAN PUPUK HIJAU OROK-OROK (CROTALARIA JUNCEA L.) DAN PUPUK NPK PHONSKA - IRAWATY ROSALYNE; ARYO VINTARIS MALAU; JONNER PURBA (JURNAL ILMIAH SIMANTEK, 2022)
This research was conducted from August to September 2020 in Persatuan Baru Village, Nagori Sigodang Barat, PaneiDistrict, Simalungun Regency with an altitude of 950 m above sea level. The purpose of this study was to determine theresponse of growth and production of Pakcoy plants to the green manure of Orok-orok and NPK Phonska. This study used arandomized block design with 2 factors, namely green manure with doses of 0 kg / ha (F1), 10 tons / ha or 4 kg / plot (F2),and 20 tons / ha or 8 kg / plot ( F3) as well as the dose of NPK Phonska fertilizer 150 kg / ha or 60 gr / plot (P1), 300 kg / haor 120 gr / plot (P2), and 450 kg / ha or 180 gr / plot (P3). Each treatment was repeated 3 times. To determine the responseto plant growth, several variables were observed, namely plant height (cm), number of leaves (strands), net weight per plantsample (gr), and net weight per plot (kg). The results of analysis of variance showed that there was a plant response to theapplication of green manure doses of Orok-orok to the addition of plant height at the age of 4 WAP, the number of plantleaves at the age of 2, 3, 4 WAP, and also to the weight per plant sample and plant weight per plot. The dosage of PhonskaNPK fertilizer shows a plant response to the increase in plant height at 4 WAP, the number of plant leaves at 2, 3, and 4WAP, and also to weight gain per plant sample, and plant weight per plot. Treatment interactions showed no significantresponse to the variables of plant height, number of leaves, net weight per sample plant and a significant response to theaddition of plant net weight per plot. The interaction of F3P2 treatment (green manure of Orok-orok 20 tons / ha and NPKPhonska 300 kg / ha) tended to be higher than the interactions of other treatments in all observation variables.